To Operation of the Uzte16m4 Diesel Locomotives on the Mountain Section of the Railway Track (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The substantiation of the parameters of the main indicators of the transportation work of diesel locomotives UzTE16M4 on a real mountain section of the railway during the movement of freight trains without stops at intermediate stations is given. Numerical values of the indicated parameters and regression equations for their definition are obtained. The results of the study are recommended for the practice of the Karshi locomotive depot of the Uzbek railway.